Green Synthesis of Selenium Nanoparticles using Allium sativum ExtractGreen Synthesis of Selenium Nanoparticles using Allium sativum Extract - Vyasa, Jay; Ranab, Shafkat (Asian Journal of Biological and Life Sciences, 2017)
The green synthesis of nanoparticles has recently gained the attention of researchers due to its eco-friendly, cost effective and non toxic nature. The present study on the reduction of Selenium ions to Selenium nanoparticles mediated through Allium sativum extract were demonstrated with an experimental procedure. The synthesized nanoparticles were characterized using UV-Visible spectrophotometer, Transmission electron microscopy (TEM), Fourier transform spectroscopy (FT-IR) and Energy dispersive X-Ray spectroscopy (EDAX). The selenium nanoparticles synthesized by Allium sativumextract observed as hollow and spherical particles in size ranging 7-48nm which found more stable more than two months.
Keywords: Allium sativum; Green synthesis; Selenium nanoparticles